Evaluating the impact of drone strikes on international humanitarian law: legal, and diplomatic perspectives - Surakka, Kevin Konstantin (Riga Graduate School of Law, 2024)
A new era of military strategy has reached new levels with the increasing deployment of drones in combat, which alters the ways in which IHL is implemented, as well as how that law is applied. The paper reviews the drone strikes’ intricate effects in the way of international humanitarian law (IHL)1, through an examination of various legal and diplomatic elements along the lines of building a scientific research related to a new aerial technology. This research is based on significant statutory instruments such as the United Nations Charter and the Geneva Conventions through combined research, case analysis, and comparative methodologies. The epicenter of this thesis is the infringement of the basic tenets of International Humanitarian Law (IHL) including but not limited to distinction, proportionality, and precaution during armed operations. The thesis infers how the subject gets complicated and diversified as technology is used in different applications by assessing the evolution and legality of drone technology in different jurisdictions.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; International humanitarian law; drones; Unmanned Aerial Vehicle; Geneva Convention; UN Charter